Higher Education and Athlete’s Second Career - Metelski, Adam (Journal of Education, Health and Sport, 2022)
Introduction and purpose. Many athletes obtain popularity during their time in sports, but what they do after the end of their professional careers is something that is rarely well known. It has to be stated that a sports career is a specific activity because it starts early in life, lasts relatively short, and the greatest successes usually occur when non-athlete peers are just starting to climb the steps of a typical professional career. Some former athletes do great after they retire from sports, but there are also many of those who have difficulties finding themselves in a new for them reality. The article aims to present how the level of education of former athletes’ affects their subsequent professional careers. Material and method. The study involved 301 former basketball players who previously played in 4 top leagues in Poland. The dependent variables in this study are the most common in the literature on the subject indicators of career success, such as earnings and job satisfaction. In turn, the independent variable is the level of education. In addition, the study considered whether the represented sports level influences the acquisition of education. Results. It turns out that those players who played in the top league finished their sports careers later and thus earned longer on basketball. However, more players from the lower leagues have higher education, and they are now more satisfied with their work. Conclusions. It may not be easy to combine professional sports at the highest level with studying. But the results of the research show that in the case of basketball, many athletes graduate from university. What is more, former players with higher education are usually very satisfied with their current job. In conclusion, it can be stated that former basketball players do well in their second careers, compared to the national average.